Vocational education and training in Lithuania : short description - (:unkn) unknown (Publications Office of the European Union, 2013)
This overview of the vocational education and training system in Lithuania is published at the time the country is taking up the Presidency of the Council of the EU (second half of 2013). It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. "Improved vocational guidance, more professional development opportunities for VET teachers and more attention to quality assurance are some of the current priorities. Although mainly school-based, IVET includes some forms of work-based learning. Apprenticeship-type training exists but is not yet very strong. The intention to include non-formally acquired qualifications in the Lithuanian qualifications framework and use of European structural Fund support are expected to help strengthen work-based learning routes." (Hrsg., BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Berufsberatung; Litauen